m-5m-4m-5=

Simple and best practice solution for m-5m-4m-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-5m-4m-5= equation:


Simplifying
m + -5m + -4m + -5 = 0

Reorder the terms:
-5 + m + -5m + -4m = 0

Combine like terms: m + -5m = -4m
-5 + -4m + -4m = 0

Combine like terms: -4m + -4m = -8m
-5 + -8m = 0

Solving
-5 + -8m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -8m = 0 + 5

Combine like terms: -5 + 5 = 0
0 + -8m = 0 + 5
-8m = 0 + 5

Combine like terms: 0 + 5 = 5
-8m = 5

Divide each side by '-8'.
m = -0.625

Simplifying
m = -0.625

See similar equations:

| 5s-7+4-2s+7z= | | x^4-18x^2+45=0 | | 39k+12=2k-11 | | m-m+4m+1= | | a=500(1+.06/2)*2 | | 3/8x-1/3+6 | | 3x-7=3(x+6) | | a=500(1+.06/2)2 | | C=8x+75 | | 9/3*(24/8) | | 16x-8-2=20 | | 9/3(24/8) | | 225-725x= | | 27/45 | | -35m-15=69 | | z^4+5iz^2+8=0 | | -4m-15=51 | | -28m-10=54 | | 7(3x/5)=11-(x/9) | | e^4x+3e^2x-18=0 | | 40x+.25y=50 | | -14m-12=79 | | cos^2(x)-sin^2(x)= | | 27y+12= | | 6x^6-9x^5-27x^4= | | 200.00+0.05s=75+0.10s | | 4x^4-4+x^3-x^2=0 | | 3x+10=5x-30 | | 24x^2+18x+5=0 | | X+34.01=44.8 | | 14+12=-15x+2 | | 3(2y-5)-2(y-4)= |

Equations solver categories